Inmate Punishments – Disciplinary Measures - Milić, Ivan; Dimovski, Darko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
After the verdict has become formal and enforceable, and the defendant a convict, sentence execution procedure follows. If the defendant is sentenced to prison, the next step to be taken is the referral institution for execution of sentence of imprisonment. Rules of conduct in the institutions for execution of imprisonment are strictly regulated by legislation governing the rights and obligations of prisoners. Conducts that are prohibited in institutions shall be prescribed as a disciplinary offense, and appropriate disciplinary measures are to be imposed. The subject of this paper are disciplinary measures stipulated by the Law on Execution of Criminal Sanctions of the Republic of Serbia. The paper gives an overview of five disciplinary measures that can be imposed for serious or minor disciplinary offenses. In particular, author focuses his attention to indicating that the imposition and execution of disciplinary measures, are not regulated by Law in the best possible way, so that, in practice, certain problems arise in the application of these measures.